Shampoodle - Holub, Joan.; Bowers, Tim (New York : Random House, 2009)
Rhyming text describes a dog grooming establishment on picture day and the uproar some curious kittens cause when they try to explore.
Horn Book, April 2010
Kirkus Review, October 2009
1.9
K-3
Keywords: Dogs -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Cats -- Juvenile fiction; Stories in rhyme; Grooming -- Fiction; Dogs -- Fiction; Animals -- Infancy -- Fiction; Cats -- Fiction; Stories in rhyme; Grooming -- Fiction; Dogs -- Fiction; Animal babies -- Fiction; Cats -- Fiction; Readers (Elementary)